POKY: a software suite for multidimensional NMR and 3D structure calculation of biomolecules - Lee, Woonghee; Rahimi, Mehdi; Lee, Yeongjoon; Chiu, Abigail (Bioinformatics (Oxford, England), 2021)
The need for an efficient and cost-effective method is compelling in biomolecular NMR. To tackle this problem, we have developed the Poky suite, the revolutionized platform with boundless possibilities for advancing research and technology development in signal detection, resonance assignment, structure calculation and relaxation studies with the help of many automation and user interface tools. This software is extensible and scalable by scripting and batching as well as providing modern graphical user interfaces and a diverse range of modules right out of the box. Poky is freely available to non-commercial users at https://poky.clas.ucdenver.edu. Supplementary data are available at Bioinformatics online.